Pengaruh Pengungkapan Sustainability Reporting Berdasarkan GRI Standards terhadap Kinerja Perusahaan pada App Group - Agus Bambang Sunyoto; Radittya Mahasputra Antara; Tutut Arif Rachman (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
Company Performance is one of the most important things for a company. Company Performance is an indicator for stakeholders because it showshow good is the company and whether to considered to invest in the company. With the phenomenon of sustainability in this era, it also determines stakeholder decisions in viewing a company, therefore stakeholders do not only look at the company's financial statements, but also the disclosure of the Sustainability Report (SR). This study examines the influence of SR disclosure on Company Financial Performance. The companies used in this study are APP Group issuer companies, namely PT. Tjiwi Kimia Paper Factory and PT Indah Kiat Pulp & Paper Tbk. Using quantitative methods with simple regression analysis. The findings of this study state that SR disclosure has no effect on the company's financial performance.